ANALISIS PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA USAHA KECIL DAN MENENGAH DI YOGYAKARTA - Koes Meiliana; A Fenyta Dewi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2015)
This study aimed to analyze the practice of the use of Accounting Information Systems (AIS) on Small and Medium Enterprises (SMEs) in Yogyakarta. In this study, analysis of the use of the SIA will be seen from the aspect of business, scale of business, company age, education owner or manager of the company, lead times, and accounting training followed by the owner or manager of the company. This research is descriptive. This research was conducted by asking questions to the respondent by distributing questionnaires. Te sampling method used is purposive sampling. Questionnaires were distributed to 100 owners or managers of SMEs in Yogyakarta, but there are six questionnaires that are not in accordance with the criteria of the sample, thus the amount of the fnal sample to 94.The results showed that the majority of SMEs in Yogyakarta have been using AIS in its operational activities. Manufacturing companies, medium-sized companies, the company that is older than 20 years, the owners or managers of companies whose educational background diploma, the owner or manager of the company that led the company for more than 5 years, the owner or manager of a company that did not get accounting training the majority of use accounting information more intensively.Keywords: Accounting Information Systems, the use of accounting information, management of operational activities, small and medium enterprises.